Correlation between academic burnout and academic resilience of undergraduate nursing students from two universities in areas with large ethnic minority populations (两所民族地区高校本科护生学业倦怠与学业复原力的相关性研究) - HAN Rui (韩蕊); DENG Jiazheng (邓家峥); HONG Yan (洪艳) (中西医结合护理)
Objective To understand the current situation of academic burnout and academic resilience of undergraduate nursing students in in areas with large ethnic minority populations, and to explore the relationship between academic burnout and academic resilience. Methods From October to December 2024, undergraduate nursing students from Inner Mongolia Minzu University and Chifeng University were selected as the survey subjects (including 461 students from Inner Mongolia Minzu University and 240 students from Chifeng University, a total of 701 students), and the general information questionnaire, academic burnout scale, and nursing student academic resilience scale were used to investigate them. Results The average score of academic burnout scale was (3. 00±0. 50), and the largest standard deviation was found in depressed mood; The average score of nursing student academic resilience scale was (3. 82±0. 70), and the largest standard deviation was found in communication. The results of the difference analysis showed that there were significant differences in academic burnout and resilience among students of different grades and genders (P＜0. 05). There was no significant independent effect of different nationalities, different origins, and whether or not they were only children on academic burnout and resilience of nursing students (P＞0. 05). The correlation coefficient between academic burnout and resilience was -0. 467 (P＜0. 01), indicating a significant negative correlation. Conclusion There are individual differences in academic burnout and academic resilience among undergraduate nursing students, and academic resilience scores have a significant negative predictive effect on academic burnout scores. Colleges and universities in areas with large ethnic minority populations should give full play to the multidisciplinary advantages of comprehensive universities, optimize nursing education and teaching, innovate the training model of nursing talents, and cultivate outstanding nursing talents in the new era with the responsibility of maintaining and promoting people's health. (目的 了解民族地区高校本科护生学业倦怠和学业复原力的现状, 并探讨学业倦怠与学业复原力的关系。方法 于2024年10月—12月选取内蒙古民族大学和赤峰学院两所高校的本科护生作为调查对象(内蒙古民族大学461名, 赤峰学院240名, 共计701名), 应用一般资料问卷、学业倦怠量表、护生学业复原力量表对其进行调查。结果 护生学业倦怠量表的平均得分为(3. 00±0. 50)分, 其中情绪低落维度的标准偏差最大; 护生学业复原力量表的平均得分为(3. 82±0. 70)分, 其中沟通维度的标准偏差最大。差异性分析结果: 不同年级、不同性别的学生在学业倦怠和学业复原力上的情况比较, 差异有统计学意义(P＜0. 05)。不同民族、不同生源地、是否独生子女的护生的学业倦怠和学业复原力比较, 差异无统计学意义(P＞0. 05); 学业倦怠与学业复原力存在明显的负相关关系(r=-0. 467, P＜0. 01)。结论 本科护生在学业倦怠和学业复原力方面存在个体差异, 学业复原力得分对学业倦怠得分有显著的负向预测作用。民族地区高校应发挥综合性大学多学科优势, 优化护理教育教学, 创新护理人才培养模式, 培养维护和促进人民健康为己任的新时代卓越护理人才。)